Pola Pemberatan Pidana dalam Hukum Pidana Khusus - Chairul Huda (Jurnal Hukum IUS QUIA IUSTUM, 2011)
What has been a fundamental issue of this study what base for the lawgivers in determining “type and number” of crime showing a disapprobation. Is there any certain pattern used by the lawgivers in determining the case in Special Criminal Code, primarily to do its weighting when compared with the general pattern used in the Criminal Code. This research was conducted by using a normative juridical method, mainly by analyzing the symptoms suggested by the legislators in the enactment of criminal threats. The results of this study indicate that in the Special Criminal Law, becoming the “symbol” of Criminal Law as the identity of Indonesia, there is no specific pattern in conducting the weighting of criminal.